The Verifiability Approach to detection of malingered physical symptoms - Boskovic, Irena (Psychology, crime & law, 2017)
Inspired by recent research showing that liars are reluctant to include verifiable details in their accounts, we explored in two studies (N = 125; N = 105) whether participants who report fabricated symptoms (‘malingerers’) present fewer verifiable details than participants who report genuine ill-health symptoms. In Study 1, participants were instructed to describe a typical day on which they had experienced a genuine or malingered symptom. Truth tellers’ statements included significantly higher proportions of verifiable details concerning the reported symptoms than malingerers’ statements. Compared with truth tellers, malingerers generated longer statements with more unverifiable details. In Study 2, we informed participants that their statements may be assessed for verifiable or checkable details. Malingerers often mentioned ‘false’ witnesses to provide checkable information and differences between malingerers and truth tellers in statement length, and checkable and uncheckable details were no longer significant. The utility and implications of the Verifiability Approach to detection of malingering are discussed.